Near Infrared Fluorescence Imaging to Demonstrate Reflux in the Superficial Microvenous Network of the Leg. (October 2022) - Hall, Nicholas; Krysa, Jolanta; Lesche, Sarah; Hill, Brigid G.; Letts, James A.; McNaughton, Andrew; Clifford, Kari; Jones, Gregory T.
Abstract : Objective: Reflux within the superficial microvenous network may play a critical role in the development of skin changes which can be associated with chronic venous insufficiency. This study aimed to determine if near infrared fluorescence (NIRF) imaging could be used to accurately determine superficial venous reflux in the leg. Methods: A total of nine limbs were examined ex vivo from patients undergoing limb amputation for peripheral arterial disease. Cannulation of the distal great saphenous vein was used to sequentially perform Xray contrast enhanced venography, NIRF imaging, and venous corrosion casts. Results: Fluorescence imaging visualised a range of different microvenous reflux patterns ex vivo, which were generally not evident by Xray venography but were consistent with retrograde resin vascular casts. These included both focal and diffuse regions of fluorescence within the skin and, consistent with previous observations, the vascular casts indicated that regions of venous reflux were typically associated with incompetent valves. Conclusion: The findings from this study suggest a potential method for investigating early stage superficial venous disease, prior to the appearance of visible signs of advanced venous disease, such as skin changes. However, further studies are required to confirm the in vivo clinical utility of these observations.